How do dutch drivers perceive horizontal curves on freeway interchanges and which cues influence their speed choice?. (July 2021) - Vos, Johan; Farah, Haneen; Hagenzieker, Marjan
Abstract: Operating speeds in Dutch freeway curves differ often by 20 km/h compared to their design speeds. Operating speed is thought to be influenced by how drivers perceive curves when approaching a curve. This explorative research explores which curve cues and other variables influence drivers' speed choice in curves. For this purpose, a survey was designed with 28 sets of curve comparisons. The curves were chosen from interchanges in the Netherlands and were compared to each other. To avoid direction bias, the curves were right turning only. In each set illustrations of two different curves out of a total of 8 curves were shown, and the participants were asked in which curve they would drive faster. In total 819 participants in the age range of 18 and 78 (mean=41.3; Std.=11.9) completed the survey. The survey data showed four common categories of curve cues and variables influencing the decision to drive faster, of which those in the category of the road environment and its surroundings were mentioned the most. The top three variables influencing speed choice are visibility of curve characteristics, "overview" as a holistic but as such hard to measure variable, and number of lanes. Variables such as presence of signage and trees were also mentioned frequently by the respondents. Geometric road characteristics such as curve radius and deflection angle were identified by the respondents as influencing variables, but only showing to affect speed selection when these are visible to the driver and not obscured by trees or other elements. This suggests combinations of geometric and surrounding elements are needed to get a better understanding of speed selection by drivers. Highlights: A survey including 28 comparisons between 8 freeway interchange curves was designed. The cues that influence drivers' speed choice on curves were identified. The top three variables influencing speed choice are visibility, "overview", and number of lanes. Visible angle is a possible generalizable holistic cue for driving faster in an upcoming curve.